Evaluation of dialysis adequacy based on Kt/V and its related factors among patients undergoing hemodialysis in Guilan dialysis centers - Seyyedeh Sahereh Mortazavi Khatibani; Maryam Yaseri; Haniyeh Sadat Fayazi; Elham Ramzanzadeh; Azin Hajipoor (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Adequate and effective dialysis can improve patients' quality of life and reduce kidney failure complications and mortality in end-stage renal disease on hemodialysis. Objectives: This study aimed to evaluate dialysis adequacy based on Kt/V and its related factors among patients undergoing hemodialysis. Patients and Methods: This cross-sectional, multi-center study was conducted during six months on hemodialysis patients referred to dialysis centers of the Guilan province in the north of Iran. Dialysis adequacy was evaluated using Kt/V (>1.2) criteria. Results: The mean Kt/V was 1.24±0.36 with a median of 1.2. Adequacy of dialysis was desirable in 51.2% of the patients. There was a significant and inverse relationship between body mass index (BMI) and Kt/V (r=-0.139, P=0.013). The relationship between Kt/V criterion and pre-dialysis weight (r=-0.310, P=0.00) and post-dialysis weight (r=-0.314, P=0.00) were inverse. The Kt/V criterion was significantly associated with calcium (Ca) level and the patients with normal Ca level had a higher adequacy than those in the other levels of Ca [normal versus low level, mean difference (MD]: 0.19±0.06; normal versus high level, MD: 0.07±0.04, P<0.001). The Kt/V criterion was inversely related to blood pressure and temperature before and after dialysis (P<0.05). Conclusion: The present study showed a close correlation between blood pressure, Ca level and BMI with dialysis adequacy based on Kt/V criteria. The findings obtained here suggested treatment strategies based on correction of Ca levels, BMI and blood pressure prior to dialysis to increase the adequacy of dialysis.